What impacts learning effectiveness of a mobile learning app focused on first-year students? - Florian Johannsen; Martin Knipp; Thomas Loy; Milad Mirbabaie; Nicholas R. J. Möllmann; Johannes Voshaar; Jochen Zimmermann (Information Systems and e-Business Management, 2023)
In recent years, the application of digital technologies for learning purposes is increasingly discussed as smartphones have become an integral part of students' everyday life. These technologies are particularly promising in the so-called "transition-in" phase of the student lifecycle when first-year students start to develop a student identity and integrate into the university environment. At that stage, most premature dropouts are observed, presumably due to a lack of self-organization or self-responsibility. Considering this, a mobile app to tackle insufficient student experiences, support learning strategies, and foster self-organization in the "transition-in" phase was developed. The research at hand proposes a generalizable success model for mobile apps with a focus on first-year students, which is based on the IS success model (Delone and McLean in Inf Syst Res 3(1):60–95, 1992) and analyzes those factors that influence student satisfaction with such an app, the intention to reuse the app, and—foremost—students' learning effectiveness. The results indicate that learning effectiveness is determined both by the perceived user satisfaction and users' intention to reuse, which are particularly influenced by perceived enjoyment but also system and information quality. Finally, design principles are derived to develop similar mobile solutions.
Keywords: 650; HCI; Learning management systems; Mobile learning; IS success model; Transition-in phase